Pemanfaatan Layanan WARINTEK (Warung Informasi dan Teknologi) di Dinas Perpustakaan dan Kearsipan Kota Padang Panjang - Taranita, Desi; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this research is: (1) describe the utilization of warintek services (technology and Information Stalls) in the service of the library and Archives of the city of Padang Panjang; (2) obstacles faced in the utilization of the service warintek (technology and Information Stalls) in the service of the library and Archives of the city of Padang Panjang; (3) attempts to overcome the obstacle of utilization of services warintek (technology and Information Stalls) in the service of the library and Archives of the city of Padang Panjang. The method of research papers using quantitative methods is done through observation field and spread the now where every question related to research issues. Based on research, things can be summed up as follows: first, with the development of information and technology, the library provides services warintek (technology and information stalls) which required a librarian or pemustaka. To provide services and information technology, librarians can leverage technology in activities such as pengkatalogan, loaning, refund, inventory, and more. However, warintek (technology and information stalls) need to be improved in terms of infrastructure and information experts. Second, the obstacles faced in carrying out library services warintek (technology and information stalls) in the service of the library and archives of the city of padang panjang are: (1) has not been the presence of officers who are experts in the field of infrormasi; (2) lack of facilities and infrastructure, such as the unavailability of a special room service warintek (technology and information stalls), lack of computers, damage that often occurs on the computer. third, the efforts made in carrying out library services warintek (technology and information stalls) in the service of the library and archives of the city of padang panjang is: (1) the parties should provide experts on library services warintek; (2) provide a special room for visitors, increase the number of computers and the library are expected soon to fix some broken computers.Keyword: library, services, utilization, Warintek.